(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The fact obtained from the research is that volleyball learning not only plays a role in improving students’ motor skills, but is also effective in instilling character values, especially honesty, discipline, responsibility, and hard work. The purpose of this study is to find out and describe the level of integration of character education values ​​through volleyball subjects at SMPN 11 Jambi City. This study aims to find out and describe how well character values ​​are integrated in volleyball learning at SMP Negeri 11 Jambi City. The method used is a descriptive quantitative approach involving 27 grade VIII students as research subjects. The results of the study revealed that the integration of character values ​​in volleyball learning is classified as good, with an average achievement of 83.2%. More specifically, the discipline indicator recorded a percentage of 84% (good), sportsmanship reached 78% (sufficient), hard work 82% (good), responsibility 85% (good), and honesty 87% (very good). The indicator with the highest achievement was honesty, while sportsmanship ranked lowest. This study concludes that volleyball learning not only serves to improve students’ technical skills but is also effective in instilling character values. On the other hand, the aspect of sportsmanship needs more attention through learning strategies that emphasize accepting defeat, controlling emotions, and respecting opponents.